Identification of Factor XIII β-Sandwich Residues Mediating Glutamine Substrate Binding and Activation Peptide Cleavage - Mohammed, Rameesa D. Syed; Piell, Kellianne M.; Maurer, Muriel C. (Thrombosis and Haemostasis, 2024)
Background Factor XIII (FXIII) forms covalent crosslinks across plasma and cellular substrates and has roles in hemostasis, wound healing, and bone metabolism. FXIII activity is implicated in venous thromboembolism (VTE) and is a target for developing pharmaceuticals, which requires understanding FXIII – substrate interactions. Previous studies proposed the β-sandwich domain of the FXIII A subunit (FXIII-A) exhibits substrate recognition sites.Material and Methods Recombinant FXIII-A proteins (WT, K156E, F157L, R158Q/E, R171Q, and R174E) were generated to identify FXIII-A residues mediating substrate recognition. Proteolytic (FXIII-A*) and non-proteolytic (FXIII-A°) forms were analyzed for activation and crosslinking activities toward physiological substrates using SDS-PAGE and MALDI-TOF MS.Results All FXIII-A* variants displayed reduced crosslinking abilities compared to WT for Fbg αC (233 – 425), fibrin, and actin. FXIII-A* WT activity was greater than A°, suggesting the binding site is more exposed in FXIII-A*. With Fbg αC (233 – 425), FXIII-A* variants R158Q/E, R171Q, and R174E exhibited decreased activities approaching those of FXIII-A°. However, with a peptide substrate, FXIII-A* WT and variants showed similar crosslinking suggesting the recognition site is distant from the catalytic site. Surprisingly, FXIII-A R158E and R171Q displayed slower thrombin activation than WT, potentially due to loss of crucial H-bonding with neighboring activation peptide (AP) residues.Conclusion In conclusion, FXIII-A residues K156, F157, R158, R171, and R174 are part of a binding site for physiological substrates [fibrin (α and γ) and actin]. Moreover, R158 and R171 control AP cleavage during thrombin activation. These investigations provide new molecular details on FXIII – substrate interactions that control crosslinking abilities.
Keywords: fibrinogen; transglutaminase; factor XIII; substrate specificity; activation peptide